1993
DOI: 10.1364/ao.32.000418
|View full text |Cite
|
Sign up to set email alerts
|

Spectral dependence of temporal point spread functions in human tissues

Abstract: We have determined the spectral dependence of the temporal point spread functions of human tissues experimentally between 740 and 840 nm in transmittance measurements on the adult head, forearm, and calf (in vivo) and the infant head (post mortem) by using picosecond laser pulses and a streak camera detector. Two parameters are extracted from the temporal point spread function; the differential path-length factor (DPF), calculated from the mean time, and the slope of the logarithmic intensity decay. In all tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(120 citation statements)
references
References 18 publications
3
116
1
Order By: Relevance
“…Duncan et al, 1995;Matcher et al, 1995a). The DPF was found to be age, gender and wavelength dependent and varies between subjects (Duncan et al, 1996;Essenpreis et al, 1993) and different tissues (Duncan et al, 1995). For example the average DPF for the adult head for 100 subjects given by Duncan et al is 6.53 ± 0.99, i.e.…”
Section: Modified Beer-lambert Law (Mbll)mentioning
confidence: 97%
“…Duncan et al, 1995;Matcher et al, 1995a). The DPF was found to be age, gender and wavelength dependent and varies between subjects (Duncan et al, 1996;Essenpreis et al, 1993) and different tissues (Duncan et al, 1995). For example the average DPF for the adult head for 100 subjects given by Duncan et al is 6.53 ± 0.99, i.e.…”
Section: Modified Beer-lambert Law (Mbll)mentioning
confidence: 97%
“…Essenpreis et al have published a DPF value of 4.48 ± 0.41 at 800 nm measured in the adult forearm assessing a gender mixed group [5], while Duncan et al found a significant gender dependence of the DPF (4.57 ± 0.74 for females and 3.75 ± 0.57 for males at 807 nm) [6]. For the arterial occlusion experiment described hereafter, the DPF values published in [6] were interpolated according to the DPF as a function of wavelength published in [5]: we used 4.48 for 760 nm and 3.81 for 870 nm. For the reconstruction of the cortical hemodynamic signals a DPF of 7.75 for 760 nm and 7.25 for 870 nm was chosen [7].…”
Section: Theorymentioning
confidence: 99%
“…Algorithms for measuring Cu A redox state changes in i o rely on converting optical density changes into the three chromophore concentration changes-deoxyhaemoglobin (Hb), oxyhaemoglobin (HbO # ) and Cu A (the other major tissue chromophore in this region, water, is presumed to maintain a constant concentration). Although the purified spectra of these compounds are well characterized, problems arise in allowing for tissue-specific effects, such as the wavelength dependence of the tochrome oxidase IRS optical path length (Essenpreis et al 1993) and possible changes in light scattering. Three algorithms, those developed at University College London (UCL) (Wray et al 1988), Keele University (Wickramasinghe et al 1990) and that used in the commercial Critikon NIRS 2000 are based on similar assumptions and would be expected to yield similar results (Matcher et al 1995).…”
Section: Algorithms For Cytochrome Oxidase Determination and Their Vamentioning
confidence: 99%